1999
DOI: 10.1007/s004290050307
|View full text |Cite
|
Sign up to set email alerts
|

Increase of segments of elastic-type blood vessel walls in fetal placental stem villi during pre-eclampsia at term

Abstract: In recent studies we described the presence of elastic-type blood vessels within trunci and rami chorii of human placental stem villi. For systemic and pulmonary hypertension it is known that elastic fibres are enhanced in arteries. The aim of our study was, therefore, to examine whether pre-eclampsia may lead to an increase of elastic tissue fibres in blood vessel walls of placental stem villi and whether there are differences in the thickness of blood vessel walls within these villi when compared to normoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…When we compared the preeclampsia group with the controls, we found an increase of wall thickness in pre-eclampsia group. Our results were in agreement with the findings of Wilhelm et al [3].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…When we compared the preeclampsia group with the controls, we found an increase of wall thickness in pre-eclampsia group. Our results were in agreement with the findings of Wilhelm et al [3].…”
Section: Discussionsupporting
confidence: 94%
“…Wilhelm et al described in their recent study that an increase of elastic tissue fibers in blood vessel walls of placental stem villi during pre-eclampsia when compared to uncomplicated pregnancies, they also described in their another study that elastic tissue fibers were decreased during pregnancies complicated by intrauterin growth retardation, independently of the occurrence of concomitant pre-eclampsia when compared to uncomplicated pregnancies [3]. Similarly, Junek et al indicated that PE induced in umblical cord arteries a decrease of elastin concentration accompanied by a thickening of both the intima and the media.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations